PENGARUH EMOTIONAL INTELLIGENCE LEADERS, PEMBERDAYAAN KARYAWAN, DAN DUKUNGAN ORGANISASI TERHADAP KEPUASAN KERJA - Dhyan Shinta Dewi, I Gusti Agung; Mudiartha Utama, I Wayan (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the influence of emotional intelligence leaders, empowering employees, and organizational support on job satisfaction at The Westin Resort Nusa Dua, Bali. Samples taken as many as 255 people using proportionate random sampling technique. The analysis technique used is multiple linear regression technique. The results of the analysis found that variables leader emotional intelligence, employee empowerment, and organizational support on job satisfaction at The Westin Resort Nusa Dua, Bali, with a contribution of 82.9 percent, while the remaining 17.1 percent is influenced by other variables not included in the model. The results showed that the variables leader emotional intelligence, employee empowerment, and support organizations and a significant positive effect on job satisfaction at The Westin Resort Nusa Dua, Bali .
Keywords: emotional intelligence leader, employee empowerment , organizational support , job satisfaction